Answer:
<h2><u>
36x
/y
</u></h2>
Step-by-step explanation:
Hope this helps
<h2><em>
:)</em></h2>
Answer: 91
Step-by-step explanation:
Given : The number of documentaries = 5
The number of comedies = 7
The number of mysteries = 4
The number of horror films =5
The total number of movies other than comedy = 14
Now, the number of possible combinations of 9 movies can he rent if he wants all 7 comedies is given by :-
![^7C_7\times^{14}C_2\\\\\dfrac{7!}{7!(7-7)!}\times\dfrac{14!}{2!(14-2)!}\\\\=(1)\times\dfrac{14\times13}{2}\\\\=91](https://tex.z-dn.net/?f=%5E7C_7%5Ctimes%5E%7B14%7DC_2%5C%5C%5C%5C%5Cdfrac%7B7%21%7D%7B7%21%287-7%29%21%7D%5Ctimes%5Cdfrac%7B14%21%7D%7B2%21%2814-2%29%21%7D%5C%5C%5C%5C%3D%281%29%5Ctimes%5Cdfrac%7B14%5Ctimes13%7D%7B2%7D%5C%5C%5C%5C%3D91)
Therefore, the number of possible combinations of 9 movies can he rent if he wants all 7 comedies is 91 .
Answer:
lollololololololol
Step-by-step explanation:
mark me brainliest :)))
<h3>
Answer: 100 meters</h3>
===========================================
Explanation:
If you draw out the diagram, then you'll find that a 45-45-90 triangle forms. The nice thing about this type of triangle is that the two legs are always the same length. The horizontal leg is 100 meters, so the vertical leg must also be 100 meters.
Side note: this type of triangle is an isosceles right triangle.
---------
You could use the tangent rule to get the same thing
tan(angle) = opposite/adjacent
tan(45) = 100/x
1 = 100/x
1*x = 100
x = 100
In this case, the opposite leg is the vertical leg since it is furthest from the angle of elevation.
Answer:
C
Step-by-step explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
Given
y = 2x² + 12x + 1
To express in vertex form use the method of completing the square.
The coefficient of the x² term must be 1 , thus factor out 2 from 2x² + 12x
y = 2(x² + 6x) + 1
add/ subtract ( half the coefficient of the x- term)² to x² + 6x
y = 2(x² + 2(3)x + 9 - 9) + 1
= 2(x + 3)² - 18 + 1
= 2(x + 3)² - 17 → C